Uji Aktivitas Antiaging Invitro Lavender Body Butter - Nutrisia Aquariushinta Sayuti (Poltekkes Kemenkes Surakarta, 2017)
Abstract : Lavender, Body Butter, Antiaging. Antiaging product must contain antioxidant and sunscreens compound to protect skin from free radical. Lavender oilwas a popular parfume of cosmetic form because of its antioxidant dan sunscreen activity. Body butter form was needed to increase antiaging activity of lavender oil. The study aimed to evaluate antiaging activity of lavender body butter trough antioxidant and sunscreen activity evaluation. Body butter was made from combination of lavender oil, olive oil, coconut oil beside cocoa butter. DPPH method was used to evaluate antioxidant activity, sunscreen activity was evaluated of the Sun Protection Factor value (SPF), the percentage of erythema transmission (%Te) and percentage of pigmentation (% Tp). The study showed that the body butter formula had IC50 of 56,34 ppm, 6,68 of %Te, 16,34 of %Tp and the SPF value was 10,88. The formula can increase lavender oil’s antioxidant and sunscreen activity and it was need the addition of chemical sunscreen compound such as Zinci Oxyde or Titanium Oxyde. It can concluded body butter had strong antioxidant activity. It can protect the skin to againt UVA ray but less protect from UVB and UVC rays.